Identification of MRAP protein family as broad‐spectrum GPCR modulators. Issue 11 (31st October 2022) - Wang, Meng; Wang, Xiaozhu; Jiang, Bopei; Zhai, Yue; Zheng, Jihong; Yang, Liu; Tai, Xiaolu; Li, Yunpeng; Fu, Shaliu; Xu, Jing; Lei, Xiaowei; Kuang, Zhe; et al.
Abstract: Background: The melanocortin receptor accessory proteins (MRAP1 and MRAP2) are well‐known endocrine regulators for the trafficking and signalling of all five melanocortin receptors (MC1R–MC5R). The observation of MRAP2 on regulating several non‐melanocortin G protein‐coupled receptors (GPCRs) has been sporadically reported, whereas other endogenous GPCR partners of the MRAP protein family are largely unknown. Methods: Here, we performed single‐cell transcriptome analysis and drew a fine GPCR blueprint and MRAPs‐associated network of two major endocrine organs, the hypothalamus and adrenal gland at single‐cell resolution. We also integrated multiple bulk RNA‐seq profiles and single‐cell datasets of human and mouse tissues, and narrowed down a list of 48 GPCRs with strong endogenous co‐expression correlation with MRAPs. Results: 36 and 46 metabolic‐related GPCRs were consequently identified as novel interacting partners of MRAP1 or MRAP2, respectively. MRAPs exhibited protein–protein interactions and varying pharmacological properties on the surface translocation, constitutive activities and ligand‐stimulated downstream signalling of these GPCRs. Knockdown of MRAP2 expression by hypothalamic administration of adeno‐associated virus (AAV) packed shRNA stimulated body weight gain in mouse model. Co‐injection of corticotropinreleasing factor (CRF), the agonist of corticotropin releasing hormone receptor 1 (CRHR1), suppressed feeding behaviour in a MRAP2‐dependent manner. Conclusions: Collectively, our study has comprehensively elucidated the complex GPCR networks in two major endocrine organs and redefined the MRAP protein family as broad‐spectrum GPCR modulators. MRAP proteins not only serve as a vital endocrine pivot on the regulation of global GPCR activities in vivo that could explain the composite physiological phenotypes of the MRAP2 null murine model but also provide us with new insights of the phenotyping investigation of GPCR–MRAP functional complexes. Abstract : We performed a single‐cell transcriptome analysis of adrenal gland and hypothalamus and drew a fine endogenous blueprint of all the emerging GPCRs and MRAP proteins. 36 and 46 metabolic‐related GPCRs were consequently identified as novel interacting partners of MRAP1 or MRAP2, respectively. Our study has comprehensively elucidated the complex GPCR networks in two major endocrine organs and redefined the MRAP protein family as broad‐spectrum GPCR modulators.